Methyl-alpha-maltoside and 5-thiomaltose: analogs transported by the Escherichia coli maltose transport system. - Ferenci, T (1980)
Neither methyl-alpha-maltoside nor 5-thiomaltose is utilized by Escherichia coli as a sole carbon source. Both are, however, effective competitive inhibitors of maltose transport into the bacterium (Km for maltose, 0.8 microM, Ki for methyl-alpha-maltoside, 5.5 microM; Ki for 5-thiomaltose, 0.2 microM). Both analogs are bound by the periplasmic maltose-binding protein. Methyl-alpha-[14C]maltoside and 5-[3H]thiomaltose were both accumulated inside E. coli. Methyl-alpha-maltoside was unchanged after accumulation, but 5-thiomaltose was converted to an unidentified compound that could exit from the bacterium. Both analogs were inhibitory to the growth of E. coli, but only when the bacteria were previously induced for the maltose transport system. The analogs are substrates for but poor inducers of the maltose transport system.